Odpowiedzi

2009-10-20T18:58:03+02:00
A) 13x -8(3x-2)=-7x-5(12-3x)
13x-24x+16=-7x -60 +15x
13x -24x +7x - 15x = -60-16
-19x = -76
x=-76/-19=4

b)7(2x-1)-6(11-x)=3(x+4)
14x-7-66+6x=3x +12
14x +6x -3x=12 +7 +66
17x=85
x=85/17=5

c)(x+5)(x+2)-3(4x-3)=(x-5)
x² +2x +5x +10-12x+9 = x-5
x² +2x+5x-12x-x= -5-10-9
x² -6x = -24
x² -6x +24 =0
Δ=6²-4*1*24 < 0 rownanie sprzeczne

d)12-2(x-1)²=4(x-2)-(x-3)(2x-5)
12- 2(x² - 2x +1) = 4x -8 - (2x² -5x -6x +15)
12 -2x² +4x -2 = 4x -8 -2x² +5x +6x -15
-11x = -8 -15 -12 +2
-11x = - 33
x= -33/-11 = 3

e) (x-3)(x+3)-(2x-1)²=x(6-3x)-9
x² -9 - (4x² -4x+1) =6x -3x²-9
x² -9 -4x² +4x -1 +3x² -6x = -9
-2x = 1
x = -0.5

f)3(x+2)²+(2x-1)²-7(x+3)(x-3)=28
3(x² +4x +4)+(4x²-4x +1) -7(x² -9) = 28
3x² +12x +12 +4x²-4x+1-7x²+63=28
8x= 28-12-1-63
x=-48/8 = -6
1 5 1